Bioenergy Development : Issues and Impacts for Poverty and Natural Resource Management - Cushion, Elizabeth; Whiteman, Adrian; Dieterle, Gerhard (World Bank, 2012)
These report overviews recent developments in the consumption and production of bioenergy. It examines the main issues and possible economic implications of these developments and assesses their potential impact on land use and the environment, especially with respect to forests. The report examines both solid biomass and liquid biofuels, identifying opportunities and challenges at the regional and country levels. The development of bioenergy presents both opportunities and challenges for economic development and the environment. It is likely to have significant impacts on the forest sector, directly, through the use of wood for energy production, and indirectly, as a result of changes in land use. The impact of bioenergy on poverty alleviation in developing countries will depend on the opportunities for agricultural development, including income and employment generation, the potential to increase poor peoples' access to improved types of bioenergy; and the effects on energy and food prices. Five main messages emerge from this report: solid biomass will continue to be a principal source of energy; developments in bioenergy will have major implications for land use; tradeoffs, including those related to poverty, equity, and the environment, must be evaluated when choosing a bioenergy system; there is considerable potential for making greater use of forestry and timber waste as a bioenergy feedstock; and the climate benefits of bioenergy development are uncertain and highly location and feedstock specific.